2008
DOI: 10.1080/13668250802010394
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, disclosure, and having autism: An interpretative phenomenological analysis of the perceptions of young people with autism

Abstract: In relation to the existing literature, it is suggested that the effects of diagnosis, or disclosure of diagnosis, from the perspective of the person with autism be given greater consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(105 citation statements)
references
References 27 publications
3
99
0
3
Order By: Relevance
“…However, little is known about the psychological consequences of receving a diagnosis in adulthood. Given the increasing number of adults seeking diagnoses, this is an area in which more research is urgently needed (Huws & Jones, 2008).…”
Section: Adult Asd Diagnosis Surveymentioning
confidence: 99%
“…However, little is known about the psychological consequences of receving a diagnosis in adulthood. Given the increasing number of adults seeking diagnoses, this is an area in which more research is urgently needed (Huws & Jones, 2008).…”
Section: Adult Asd Diagnosis Surveymentioning
confidence: 99%
“…Parents of children with autism, and adults with autism, report feelings of relief following diagnosis (Brogan and Knussen, 2003;Williams, 2004). The findings of Huws and Jones (2008), however, highlighted how young people's views can differ significantly to those of parents, therefore emphasising the importance of seeking their views.…”
Section: Introductionmentioning
confidence: 97%
“…Acknowledging the 'autistic way of thinking' (Whitaker, 2006) and putting this at the centre of the research process was considered essential to understand the diagnostic experiences. Evidence has therefore been sought from the population whose views it seeks to explore (Huws and Jones, 2008). Systematic analysis has been undertaken to enable interpretation to be developed around the participants' experiences while also taking account of the complexity of such experiential data (Strauss and Corbin, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…One participant's comment that they were relieved that their difficulties were not due to a faulty character is an echo of existing research, which found similar expressions of relief and being able to redefine their 'self' (Punshon, Skirrow, Murphy, 2009). Their experiences were also reflective of a study on the experience of diagnosis for young people with autism, which suggested that themes such as 'disclosure delay' and 'providing explanations' were equally salient to receiving the diagnosis at a young age (Huws & Jones, 2008).…”
Section: Effects Of the Diagnosismentioning
confidence: 99%
“…A small number of qualitative studies aim to explore the lived experiences of children and adults with autism (Hurlbutt & Chalmers, 2002;Jones, Quigney, & Huws, 2003;Huws & Jones, 2008;Preece & Jordan, 2009;Jones, Zahl & Huws, 2010). This current study forms part of an ongoing exploratory research into the lived experiences of older adults with autism in the UK.…”
Section: Introductionmentioning
confidence: 99%